Partial purification of proteolytic enzymes and characterization of trypsin from merluccius hubbsi by-products - Lamas, Daniela Lorena (2015)
Proteolytic enzymes have been detected and partially purified from Merluccius hubbsiviscera. Crude proteinase extract exhibited its maximal activity at pH 7.94, 59.52ºC and33.93 minutes using azocaseín as a substrate. The molecular weight was estimated to be 25kDa by SDS-PAGE. The best ratio of crude extract to cold acetone for the partial purificationof protease was found in 1:1.25 with a 94.02% of recovery.Results relative to the substrate specific BAPNA, indicated that the recovered protease was atrypsin. The kinetic trypsin constant Km and kcat were 0.38 mM and 0.97/s respectively,while the catalytic efficiency was 2.54/mMs. The stability results obtained with surfactantssuggest that this enzyme can be incorporated as an ingredient in detergent formulations.